Risk of mortality in the elderly with different degree of sensorineural hearing loss in Taiwan - Chen, Jin-Cherng; Hsieh, Pei-Shan; Hwang, Juen-Haur (Frontiers in Neurology, 2025)
IntroductionSensorineural hearing loss (SNHL) may lead to disability in many aspects. This study aims to investigate the risk of mortality in the elderly with sensorineural hearing loss (SNHL) in Taiwan.MethodsThree hundred and eighteen subjects with SNHL of age between 51 and 88 years old were included between August 2000 and December 2002. Averaged pure tone threshold of all tested six frequencies (250 Hz, 500 Hz, 1,000 Hz, 2000 Hz, 4,000 Hz, and 8,000 Hz) of both ears with all audiogram shapes was divided into three cohorts: normal hearing group [0–24 decibel hearing level (dBHL)]; mild SNHL group (25–39 dBHL); moderate and severe SNHL group (40–89 dBHL). The incidence rates of mortality were compared using the Kaplan–Meier method with the log-rank test. Association of SNHL and mortality was examined by a Cox proportional hazard model with adjustment for all covariates.ResultsCompared to the normal hearing group, the crude hazard ratio (HR) and adjusted hazard ratio (aHR) for mortality in mild SNHL group was 1.51 (95% CI = 0.44–5.14, p = 0.5143) and 2.14 (95% CI = 0.45–10.23, p = 0.3396), respectively. And, the crude HR and aHR for mortality in moderate and severe SNHL group was 4.82 (95% CI = 1.65–14.07, p = 0.0041) and 6.96 (95% CI = 1.60–30.23, p = 0.0096), respectively.ConclusionThe risk of mortality was significantly higher in the elderly with moderate and severe SNHL.